2017
DOI: 10.1186/s12905-017-0428-5
|View full text |Cite
|
Sign up to set email alerts
|

Frequency and genotypes of Chlamydia trachomatis in patients attending the obstetrics and gynecology clinics in Jalisco, Mexico and correlation with sociodemographic, behavioral, and biological factors

Abstract: Background Chlamydia trachomatis is the causative agent of the most common bacterial sexually transmitted infection worldwide. The aim of this study was to investigate the frequency and genotypes of C. trachomatis in patients attending an obstetrics and gynecology clinic in Jalisco, Mexico and correlates them with sociodemographic, behavioral, and biological factors.Methods C. trachomatis detection was performed in endocervical samples from 662 patients by direct fluorescence assay (DFA) and two PCR assays tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
11
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 41 publications
(38 reference statements)
6
11
0
2
Order By: Relevance
“…Besides, 97% of infected cases were identified in participants never tested before in the current study, indicating that a large numbers of patients would be missed due to the poor screening. Consistent with most studies nowadays [34, 46, 4850], education and occupation were not found to be significant risk factors of CT infection in our study. In the past, the spread of STD prevention knowledge mainly relies on traditional media, such as books and poster foldouts, which were usually more accessible to people with higher education and occupation.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Besides, 97% of infected cases were identified in participants never tested before in the current study, indicating that a large numbers of patients would be missed due to the poor screening. Consistent with most studies nowadays [34, 46, 4850], education and occupation were not found to be significant risk factors of CT infection in our study. In the past, the spread of STD prevention knowledge mainly relies on traditional media, such as books and poster foldouts, which were usually more accessible to people with higher education and occupation.…”
Section: Discussionsupporting
confidence: 89%
“…Our study showed that 10.6% of men and 10.3% of women attending sexual and reproductive health clinics were tested positive for CT infection, similar to that reported in England (10.3%-10.6%) [38,40], Netherlands (8.9%-10.1%) [41], Nigeria (9.6%) [42], Danmark (11.5%) [43], Spain (12.3%) [44], Iran (12.6%) [45], and Mexico (14.2%) [46]. However, the prevalence of CT infection in the current study was higher than that reported in Australia (5.9%) [47] and lower than that reported in Ethiopia (18.9%) [48], Palestine (20.2%) [49] and Solomon Islands(20.3%) [50].…”
Section: Discussionsupporting
confidence: 83%
“…Regarding vaginal discharge reported by pregnant women as a frequent reason for hospitalization, it is important to note that increased vaginal discharge in pregnant women is common; however, vaginal discharge can be a warning sign for the presence of infections that can complicate gestation and delivery such as candidiasis, chlamydia, trichomoniasis, and bacterial vaginosis. Thus, the early diagnosis of these infections in pregnant women is essential to avoid complications, especially for newborns (19) .…”
Section: Discussionmentioning
confidence: 99%
“…WHO reports that about 130 million new cases of infection with this pathogen occur worldwide each year (Newman et al., 2015). For example, in Mexico, the infection prevalence among women is reported between 3% and 19% (Casillas et al., 2017; López‐Hurtado, García, Escobedo, Bustos, & Guerra, 2018) while the infection prevalence among men is reported between 3.6% and 31.9% (Guerra‐Infante, Tapia, López, Flores, & Díaz, 2005; López‐Hurtado, Velazco, et al, 2018). It is well documented that CT infection among women develops pelvic inflammatory disease, tubal occlusion and ectopic pregnancies while among men the CT infection causes nongonococcal urethritis, epididymitis and orchitis.…”
Section: Introductionmentioning
confidence: 99%